OPTIMALISASI USAHA TANAMAN HIAS DENGAN KENDALA FAKTOR PRODUKSI - Zainal Abidin; Darmiati Dahar; S Syamsir; Rahmat Badu (Fapetrik-UMPAR, 2022)
The ornamental plant business in West Pentadio Village, Telaga Biru District, Gorontalo Regency, has excellent opportunities. This study aimed to determine the optimal conditions for ornamental plant business with production factor constraints. The data collection method used the Purposive Sampling method with samples selected based on the most produced plants. The sample in this study was the Wawan Bunga ornamental plant business in Pentadio Village. Research data were analyzed quantitatively descriptively using Linear Programming. The research results show that this ornamental plant business could be more optimal. The optimal income of IDR 11,242,000 is greater than the actual income, which is only IDR 10,455,000. The remaining land of 0.02047 Ha and capital of IDR 1,415,000 has not been used optimally. The use of labor in May, June, November, and December amounted to 21 HOK, which exceeded the NRK limit. As well as for interest X1, X6, X8, and X10 can affect the optimal income of Rp. 2,808,000, Rp. 5,024,000, Rp. 2,908,000 and Rp. 2,400,000, which has a sizeable Reduced Cost value.